1999
DOI: 10.1007/s002130050994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social isolation on the metabolism of morphine and its passage through the blood-brain barrier and on consumption of sucrose solutions

Abstract: We conclude that the behavioural effect of isolation observed in the conditioned place preference to morphine may depend on changes both in morphine disposition and in the sensitivity to reinforcers in isolated mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We also observed that adding sucrose to the drinking water, in the absence of analgesic drugs did not increase water consumption (Supplementary File 1A,E). This seems to contradict publications that demonstrated that mice prefer to drink sweetened water [48,61,62]. The C57Bl/6J mouse strain was reported to be especially susceptible to sweetened water, when compared to other mouse strains [46,47].…”
Section: Discussionmentioning
confidence: 68%
“…We also observed that adding sucrose to the drinking water, in the absence of analgesic drugs did not increase water consumption (Supplementary File 1A,E). This seems to contradict publications that demonstrated that mice prefer to drink sweetened water [48,61,62]. The C57Bl/6J mouse strain was reported to be especially susceptible to sweetened water, when compared to other mouse strains [46,47].…”
Section: Discussionmentioning
confidence: 68%
“…(1997) had shown that morphine CPP was observed in social mice at the dose of 8 mg/kg, whereas 4 weeks of isolation impaired morphine (8–100 mg/kg ip) place conditioning. In a follow‐up to this study, Coudereau et al . (1999) further investigated this phenomenon and tested three possible explanations: a reduced sensitivity to reinforcers induced by isolation; a difference in morphine disposition in isolated and social mice; and an altered blood–brain barrier transport of morphine in isolated mice.…”
Section: Methodological Issuesmentioning
confidence: 72%
“…Group-housed and singly housed rodents have been found to differ with respect to behavioral and neurochemical effects of drugs. Singly housed rodents tend to be more sensitive than grouphoused rodents to certain drugs (e.g., Cheeta et al 2001;Coudereau et al 1999). Furthermore, defeated or subordinate rodents differ in sensitivity to drugs compared to residents or dominant rodents.…”
Section: Introductionmentioning
confidence: 99%